Teknik Pembibitan Tanaman Kapuk Randu (Ceiba pentandra L.) di UPTD BSPTH Dinas Kehutanan Provinsi Sumatera Barat - Alya Fitriani; Filza Yulina Ade; Mika Lestaria (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Kapok randu (Ceiba pentandra L.) is a tropical tree species from the family Malvaceae that holds significant economic and ecological value, particularly in supporting reforestation and sustainable forest management programs. The success of kapok randu cultivation is strongly determined by the quality of seedlings produced during the early growth phase. This study aims to describe the seedling techniques of kapok randu applied at the UPTD Balai Sertifikasi dan Perbenihan Tanaman Hutan (BSPTH) of the West Sumatra Provincial Forestry Service. The method used was direct observation of each seedling stage, including seed soaking, seedling media preparation, sowing, seedling maintenance, and transfer to polybags. The results showed that soaking seeds for 12–24 hours effectively softened the hard seed coat and supported the germination process. Sowing in a mixture of soil and rice husk under shaded conditions, combined with routine watering, successfully supported the gradual emergence of shoots and young leaves. The seedling techniques applied at UPTD BSPTH were found to be effective in supporting the early growth of kapok randu seedlings and can serve as a reference for further seedling and cultivation activities.